Electron Dynamics Within the Electron Diffusion Region of Asymmetric Reconnection. Issue 1 (4th January 2018) - Argall, M. R.; Paulson, K.; Alm, L.; Rager, A.; Dorelli, J.; Shuster, J.; Wang, S.; Torbert, R. B.; Vaith, H.; Dors, I.; Chutter, M.; Farrugia, C.; et al.
Abstract: We investigate the agyrotropic nature of electron distribution functions and their substructure to illuminate electron dynamics in a previously reported electron diffusion region (EDR) event. In particular, agyrotropy is examined as a function of energy to reveal detailed finite Larmor radius effects for the first time. It is shown that the previously reported ∼66 eV agyrotropic "crescent" population that has been accelerated as a result of reconnection is evanescent in nature because it mixes with a denser, gyrotopic background. Meanwhile, accelerated agyrotropic populations at 250 and 500 eV are more prominent because the background plasma at those energies is more tenuous. Agyrotropy at 250 and 500 eV is also more persistent than at 66 eV because of finite Larmor radius effects; agyrotropy is observed 2.5 ion inertial lengths from the EDR at 500 eV, but only in close proximity to the EDR at 66 eV. We also observe linearly polarized electrostatic waves leading up to and within the EDR. They have wave normal angles near 90°, and their occurrence and intensity correlate with agyrotropy. Within the EDR, they modulate the flux of 500 eV electrons travelling along the current layer. The net electric field intensifies the reconnection current, resulting in a flow of energy from the fields into the plasma. Plain Language Summary: The process of reconnection involves an explosive transfer of magnetic energy into particle energy. When energetic particles contact modern technology such as satellites, cell phones, or other electronic devices, they can cause random errors and failures. Exactly how particles are energized via reconnection, however, is still unknown. Fortunately, the Magnetospheric Multiscale mission is finally able to detect and analyze reconnection processes. One recent finding is that energized particles take on a crescent‐shaped configuration in the vicinity of reconnection and that this crescent shape is related to the energy conversion process. In our paper, we explain why the crescent shape has not been observed until now and inspect particle motions to determine what impact it has on energy conversion. When reconnection heats the plasma, the crescent shape forms from the cool, tenuous particles. As plasmas from different regions mix, dense, nonheated plasma obscures the crescent shape in our observations. The highest‐energy particle population created by reconnection, though, also contains features of the crescent shape that are more persistent but appear less dramatically in the data. Key Points: We study agyrotropy and energy dissipation in an EDR event on the ion and electron inertial scales Agyrotropy is observed 2.5 ion inertial lengths from the X point at energies above the electron crescent population Amplitude and occurrence of electrostatic, linearly polarized waves near f ce correlate with increased agyrotropy in and around the EDR